The Influence Of Digital Marketing On Tokopedia - Wuladari, Fithri (Yayasan Pendidikan Belajar Berdikari, 2024)
One of the earliest mobile e-commerce sites in Southeast Asia, including Indonesia, was Tokopedia. Digital marketing on the Tokopedia platform is utilised as a tactic to draw in new customers in the face of E-commerce rivalry. Thus, the purpose of this study was to ascertain how digital marketing via electronic word-of-mouth affected the Tokopedia platform. With a sample of 87 respondents, this study employs quantitative and descriptive research approaches. Non-probability sampling utilising the path analysis method is the sample strategy employed. SPSS version 25 was used for data processing. According to the study's findings, purchasing decisions are significantly influenced by digital marketing.